The KKLMMT Scenario for Inflation and Generalizations - Năstase, Horaţiu [UNESP] (My University, 2019)
In the previous chapter, we have shown how KKLT have obtained a de Sitter background in string theory, with a geometry made from branes, cut off in the UV and smoothly joined onto a CY3 half of space, and an antibrane at the tip (minimum of the KS throat). In this chapter, we will present the KKLMMT scenario for string inflation based on it, of the type of brane-antibrane inflation already analyzed before in the book.